Work shift duration: a review comparing eight hour and 12 hour shift systems - Smith, L. (BMJ Group, 1998)
OBJECTIVES: Shiftwork is now a major feature of working life across a broad range of industries. The features of the shift systems operated can impact on the wellbeing, performance, and sleep of shiftworkers. This paper reviews the current state of knowledge on one major characteristic of shift rotas-namely, shift duration. Evidence comparing the relative effects of eight hour and 12 hour shifts on fatigue and job performance, safety, sleep, and physical and psychological health are considered. At the organisational level, factors such as the mode of system implementation, attitudes towards shift rotas, sickness absence and turnover, overtime, and moonlighting are discussed. METHODS: Manual and electronic searches of the shiftwork research literature were conducted to obtain information on comparisons between eight hour and 12 hour shifts. RESULTS: The research findings are largely equivocal. The bulk of the evidence suggests few differences between eight and 12 hour shifts in the way they affect people. There may even be advantages to 12 hour shifts in terms of lower stress levels, better physical and psychological wellbeing, improved durations and quality of off duty sleep as well as improvements in family relations. On the negative side, the main concerns are fatigue and safety. It is noted that a 12 hour shift does not equate with being active for only 12 hours. CONCLUSIONS: There can be considerable extension of the person's time awake either side of the shift. However, the effects of longer term exposure to extended work days have been relatively uncharted in any systematic way. Longitudinal comparative research into the chronic impact of the compressed working week is needed.